Effects of nutrient and light enrichment on phytoplankton growth - Domingues, Rita B. (2012)
Alterations of freshwater flow regimes and increasing eutrophication lead to alterations in light availability and nutrient loading into adjacent estuaries and coastal areas. Phytoplankton community respond to these changes in many ways. Harmful phytoplankton blooms, for instance, may be a consequence of changes in nutrient supply, as well as the replacement of some phytoplankton species (like diatoms, that contribute for the development of large fish and shellfish populations) by ohers (like cyanobacteria, that may be toxic and represent an undesirable food source for higher trophic levels). Nutrient and light enrichment experiments allow us to understand and predict the effects of eutrophication on the growth of phytoplankton. This is a fundamental tool in water management issues, since it enables the prediction of changes in the phytoplankton community that may be harmful to the whole ecosystem, and the design of mitigation strategies (Zalewski 2000).